2019
DOI: 10.1002/psp4.12447
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically‐Based Pharmacokinetic Modeling of Atorvastatin Incorporating Delayed Gastric Emptying and Acid‐to‐Lactone Conversion

Abstract: The drug–drug interaction profile of atorvastatin confirms that disposition is determined by cytochrome P450 (CYP) 3A4 and organic anion transporting polypeptides (OATPs). Drugs that affect gastric emptying, including dulaglutide, also affect atorvastatin pharmacokinetics (PK). Atorvastatin is a carboxylic acid that exists in equilibrium with a lactone form in vivo. The purpose of this work was to assess gastric acid–mediated lactone equilibration of atorvastatin and incorporate this into a physiologically‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
(110 reference statements)
0
22
0
Order By: Relevance
“…With few exceptions, the PK studies reported to date consist mainly in classical association studies using noncompartmental PK analysis sometimes performed on healthy volunteers after single dose administration 21,28,32,[35][36][37] or physiologically-based PK models. [40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…With few exceptions, the PK studies reported to date consist mainly in classical association studies using noncompartmental PK analysis sometimes performed on healthy volunteers after single dose administration 21,28,32,[35][36][37] or physiologically-based PK models. [40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…In addition, because ATV is known to be transported by P-glycoprotein, Oatp2b1, Bcrp and Mrp2 on intestinal epithelial cells and Oatp1b2 on hepatocyte and to be transformed to the major metabolite o -ATV and minor metabolite p -ATV by Cyp3A1 in liver (Morse et al. 2019 ), we also analysed expression of these gene products. Notably, because studies have shown that the promoter region of Cyp3A1 is more similar to that of CYP3A4 than Cyp3A2 , many other researchers have only examined the Cyp3A1 subtype, however, we investigated both Cyp3A1 and Cyp3A2 due to their 88% identity (Takada et al.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism is modelled through enzyme kinetics in all cases and mainly by means of CYP3A4. However, some models use another CYP isoform (CYP2C8 in Zhang, 2015) or an unspecific metabolism through HLM (Morse et al, 2019). Lactonization is modelled enzymatically through UGT1A1 and UGT1A3 in the models of Zhang and Li et al, while it is considered to occur non-enzymatically in the stomach in Morse et al As both processes have been demonstrated to contribute to ATS-L formation, any PBPK model of ATS should consider them to best reproduce the PK of ATS.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first PBPK model that considers pre-systemic degradation of ATS [ 78 ]. The model developed by Morse et al states that ATS-L is mostly formed non-enzymatically in the stomach due to the low pH of this region of the GI tract.…”
Section: Physiologically Based Pharmacokinetic Models Of Atorvastatinmentioning
confidence: 99%